Knowledge Requirements Fulfillment Analysis - Randles, Theodore J.; Gardner, Lisa A.; Zhang, Zhe (American Journal of Management, 2023)
The knowledge spectrum organizes a large amount of information about knowledge, dividing intelligent behavior into its cognitive elements. By providing a concise way to describe organization knowledge requirements and resources, the spectrum supports their cataloging, measurement, and analysis. Obtaining information about knowledge requirements begins with a few simple queries. Business process managers would be asked to identify the maps that guide the performance of the processes that they manage. The dialogue that enables the definition of knowledge requirements, the creation of business process knowledge requirements (BPKR) trees, and the creation of employee knowledge profiles is described. The levels and branches of a BPKR tree and the information stored in BPKR trees is explained. Using several examples from information systems, the value of business process knowledge requirements (BPKR) trees is illustrated. How these trees support the conduct of knowledge requirements fulfillment analysis (KRFA) is described. Although simple, the examples will demonstrate that KRFA should enable firms to better match knowledge requirements and resources. A prototype system for KRFA is briefly described.